Effects of strength training and raloxifene on femoral neck metabolism and microarchitecture of aging female Wistar rats. Issue 1 (December 2017) - Stringhetta-Garcia, Camila; Morais, Samuel; Fernandes, Fernanda; Perez-Ueno, Melise; Almeida, Ricardo; Louzada, Mário; Chaves-Neto, Antonio; Ervolino, Edilson; Dornelles, Rita
Abstract The aim of this study was to prevent female osteoporosis using strength training (ST), raloxifene (Ral) or a combination of ST plus Ral during the natural female aging process, specifically in the periestropause period. For a total of 120 days, aging female Wistar rats at 18-21 months of age performed ST on a ladder three times per week, and Ral was administered daily by gavage (1 mg/kg/day). Bone microarchitecture, areal bone mineral density, bone strength of the femoral neck, immunohistochemistry, osteoclast and osteoblast surface were assessed. We found that the treatments modulate the bone remodeling cycle in different ways. Both ST and Ral treatment resulted in improved bone microarchitecture in the femoral neck of rats in late periestropause. However, only ST improved cortical microarchitecture and bone strength in the femoral neck. Thus, we suggest that performing ST during the late period of periestropause is a valid intervention to prevent age-associated osteoporosis in females.